Mucosal Melanoma of the Oral Cavity: What is the Role of Elective Neck Dissection?. (13th May 2022) - Haimowitz, Sean; Cohen, David A.; Dhanda, Aatin; Barron, Kendyl; Povolotskiy, Roman; Roden, Dylan
Abstract : Objectives: Mucosal melanoma (MM) is a rare malignancy that can present in the head and neck (H&N). The Oral cavity is the second most common primary site in the H&N after sinonasal mucosa. This study investigates the impact of demographic and clinical factors on survival in oral cavity MM. Further, it investigates the outcomes and utility of elective neck dissections (END) in the management of oral MM. Methods: The National Cancer Database was used to evaluate 432 patients with oral cavity MM from 2004 to 2016. Kaplan‐Meir and Cox regression analyses were used to determine variables associated with survival. Results: The mean age was 64.0 ± 16.0 years. Most patients were white (85.1%) and male (60.0%). Gingiva (37.6%) and hard palate (36.1%) were the most common primary subsites in the oral cavity. Five‐year overall survival was 31.0%. Age (Hazards Ratio [95% Confidence Interval], 1.03 [1.01–1.06]), N‐stage (1.94 [1.10–3.42]), M‐stage (10.13 [3.33–30.86]), male sex (1.79 [1.06–3.03]), and African‐American race (2.63 [1.14–6.11]) were significantly associated with worse survival. 199 patients (46.9%) underwent neck dissection including 118 with lymph node yield (LNY) ≥ 18. The rate of occult nodal positivity was 45.4% for LNY ≥ 18 and 28.3% for LNY ≥ 1. ENDs were not associated with improved outcomes. However, occult lymph node involvement was associated with worse overall survival ( p = 0.004). Conclusions: Oral cavity MM has a poor prognosis. Lymph node involvement, distant metastasis, age, race, and male sex are associated with worse outcomes. Performing an END did not improve survival. However, END may have a prognostic role and help select patients for treatment intensification. Level of Evidence: 4 Laryngoscope, 133:317–326, 2023 Abstract : This study uses the National Cancer Database to analyze factors associated with survival in oral cavity mucosal melanoma, as well as the role of elective neck dissections. Lymph node involvement, distant metastasis, age, race, and male sex were associated with worse outcomes. While elective neck dissections did not improve overall survival, they may have a prognostic role and help select patients for treatment intensification.